2013
DOI: 10.1111/jcmm.12175
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MAPK‐mediated ACE expression by compound C66 prevents STZ‐induced diabetic nephropathy

Abstract: A range of in vitro, experimental and clinical intervention studies have implicated an important role for hyperglycaemia-induced activation of the renin-angiotensin system (RAS) in the development and progression of diabetic nephropathy (DN). Blockade of RAS by angiotensin converting enzyme (ACE) inhibitors is an effective strategy in treating diabetic kidney diseases. However, few studies demonstrate the mechanism by which hyperglycaemia up-regulates the expression of ACE gene. Our previous studies have ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 41 publications
0
53
0
Order By: Relevance
“…In a model of diabetic renal fibrosis induced by streptozotocin (STZ), C66, a curcumin analog, blocked glomerular and interstitial fibrosis, which was associated with reduced renal mitogen activated protein kinase (MAPK) signaling [53, 54]. Chromatin immunoprecipitation (ChIP) revealed that C66 reduced STZ-mediated recruitment of p300 to the promoters for the genes encoding CTGF, PAI-1 and fibronectin, and this was associated with reduced H3K9/14 acetylation at these sites.…”
Section: Histone Acetyltransferases (Hats) and Fibrosismentioning
confidence: 99%
“…In a model of diabetic renal fibrosis induced by streptozotocin (STZ), C66, a curcumin analog, blocked glomerular and interstitial fibrosis, which was associated with reduced renal mitogen activated protein kinase (MAPK) signaling [53, 54]. Chromatin immunoprecipitation (ChIP) revealed that C66 reduced STZ-mediated recruitment of p300 to the promoters for the genes encoding CTGF, PAI-1 and fibronectin, and this was associated with reduced H3K9/14 acetylation at these sites.…”
Section: Histone Acetyltransferases (Hats) and Fibrosismentioning
confidence: 99%
“…We have synthesized a few of novel curcumin analogues . Among these analogues, C66 was found to effectively inhibit high glucose (HG)‐induced inflammatory response and macrophage infiltration, resulting in a significant prevention of renal injury in diabetic rats . However, whether C66 is able to prevent diabetes‐induced vascular damage via up‐regulation of Nrf2 and its downstream antioxidant proteins has not been addressed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation initiates the progress of renal abnormal homeostasis leading to acute and chronic renal damages. 20,21 Macrophage infiltration was significantly correlated with the extent of glomerulosclerosis, interstitial fibrosis and glomerular hypertrophy in human renal injuries. 28 Previous findings have supported that proinflammatory cytokines, such as TNF-α, IL-6 and iNOS, obviously increased in obese mouse proximal tubule and glomerular cells.…”
Section: Discussionmentioning
confidence: 97%
“…Compared with lean mice, the mRNA of Klf4 was time dependently decreased in HFD-fed mice ( Figure 1A). [19][20][21][22] As showed in Figure 1D Circulating creatinine and blood urea nitrogen (BUN) are crucial parameters for defining renal dysfunction.…”
Section: Decreased Levels Of Klf4 Were Positively Associated With Rmentioning
confidence: 99%
See 1 more Smart Citation